Potential of Trichocompost to Improve Organic Garlic Production in Fusarium Wilt–Endemic Fields in Tawangmangu, Central Java - Susilo Hambeg Poromarto; Supyani Supyani; Salim Widono; Dwiwiyati Nurul Septariani; Hadiwiyono Hadiwiyono; Argha Hyta Dimas Enggartiasto (Journal of Biodiversity and Biotechnology, 2025)
Garlic is a high-value commodity in Tawangmangu, one of its major production centers in Central Java. However, productivity in this region is seriously affected by Fusarium, the pathogen causes basal rot and wilting in the upper parts of the plant. The disease known as basal rot or Fusarium wilt, with the disease intensity in the field can exceeding  60%. Currently, chemical control remains the primary management strategies, which in organic farming, this practice is not acceptable. Therefore, environmentally friendly alternatives are required, such as using organic fertilizers, biological control agent like Trichoderma or combination. Trichoderma is also known as a cellulolytic microbe, which can enhance the composting process and produce Trichompost with improved quality. Field experiment results indicate that Trichocompost (TC) performs better compared to compost (C), Trichoderma (T), or untreated treatment. This findings suggest that garlic treated with Trichocompost and organic fertilizer show better growth with lower wilting intensity. Therefore, there is an indication that increased plant growth can reduce the intensity of Fusarium wilt in garlic.